The Role of Social Support for Academic Burnout in Active Students at the Faculty of Psychology, State University of Makassar - Fitriani, Nurul; Akmal, Nur; Tenriawaru Ahmad, Astiti (Polteknik Ilmu Pemasyarakatan, 2025)
Social support can play an important role in reducing the risk of academic burnout by providing emotional, informational, and instrumental resources. This research aims to examine the role of social support on the level of academic burnout in active students at the Faculty of Psychology, Makassar State University. This research uses a quantitative approach with a survey method involving 305 students from the Faculty of Psychology as respondents using non-probability accidental techniques. Data was collected using a Likert scale questionnaire, then analyzed using linear regression. The results of the hypothesis test show an R-square value of 0.173 (17.3%), which indicates that social support has a significant influence on reducing the level of academic burnout in students. The implication of this research is that faculties need to implement social support programs that are acceptable to students, and institutions must consider policies that encourage interaction between students and with the people around them. This research opens up opportunities for further study regarding the types of support that have the most significant impact on students' lives and expands investigations into other factors that influence academic burnout.